ENCYCLICAL OF PIUS XII "HUMANI GENERIS" AS A DEFENSE OF TRADITION AND DEFINING THE FRAMEWORK FOR RESPONDING TO THE CHALLENGES OF SCIENCE - Kupiński, Krzysztof (Studia Teologiczne Białystok Drohiczyn Łomża, 2025)
The encyclical Humani Generis, promulgated by Pius XII in 1950, is a pivotal document of the 20th-century Church. It reflects the challenges and tensions between traditional doctrine and contemporary natural sciences and philosophy. Defending orthodoxy, it criticized dogmatic relativism, promoted Thomistic philosophy, and rejected polygenism while allowing the hypothesis of human bodily evolution. Emerging amid renewal movements like Nouvelle Théologie, which it initially curtailed, it ultimately contributed to their rehabilitation and the Second Vatican Council. Today, its reflections on faith and reason remain relevant amid biotechnology and questions of human identity, highlighting the need for dialogue between theology and science.